The Effect of Digital Transformation on Branch Performance Through Strategic Capabilities and Execution Capabilities in The Indonesian Banking Sector - Bontor Sitio; Sabrina Oktaria Sihombing (Universitas Wiralodra, 2026)
This study seeks to analyze the impact of digital transformation on branch performance, taking into account the mediating roles of strategy and execution skills within the Indonesian banking sector. A quantitative methodology utilizing Partial Least Squares–Structural Equation Modeling (PLS-SEM) was implemented. Data were gathered from 204 responders representing bank branches that have adopted digital banking services. The research instrument consisted of four primary constructs, with indicators confirmed using measurement and structural model assessments to guarantee reliability and validity. The findings demonstrate that digital transformation significantly influences both strategy and execution skills, although does not directly impact branch performance. Moreover, execution capabilities substantially impact branch performance and serve as the principal mediating mechanism connecting digital transformation to branch performance, while strategic capabilities do not demonstrate a major mediating function. These findings emphasize that enhancements in branch performance within digital banking are significantly contingent upon an organization’s capacity to proficiently implement strategies, rather than only on strategic planning or the integration of digital technologies.